Assessment of Power Quality for Large Scale Utility Grid-Connected Solar Power Plant Integrated System - Ahmed Haji; Mehdi F. Bonneya (Journal of Techniques)
This paper introduces the simulation and analysis of a three-phase large-scale grid-connected solar Photovoltaic (PV) system in order to assess the effect of integrated PV grid-connected mode on the power quality of the utility grid. The study takes into account the effect of solar system power variation as well as the PV inverter's introduction of penetrating harmonics into the system. The simulation of the system is done in MATLAB software using the SIMULINK environment and is tested by the Pysyst program. Where it is done in real-time with an actual case study on a 1620-kW PV array connected to an 11-kV grid via a three-level Voltage Source Converter (VSC). The technical data was recorded, and the system's power quality was examined. The grid-connected PV system's Performance Ratio (PR) is assessed to determine the PV system's reliability and grid connectivity.